Pharmacognostic Analysis of Medicinal Plants Containing Essential Oils - Soliyeva Dilafruz Shavkatbek kizi (Zien Journals, 2023)
This review aims to survey the major pharmacognostic plant taxa containing essential oils of pharmaceutical interest. The botanical families covered include Lamiaceae, Rutaceae, Myrtaceae, Zingiberaceae, Apiaceae, and Asteraceae among others. For each family, the major essential oil-bearing genera and species will be discussed along with the characteristic chemical constituents of their volatile oils. The pharmacological activities attributed to these essential oils will also be overviewed
Keywords: Essential oils; medicinal plants; pharmacognosy; monoterpenes